2015
DOI: 10.1371/journal.pone.0117472
|View full text |Cite
|
Sign up to set email alerts
|

Androgen Receptor and Histone Lysine Demethylases in Ovine Placenta

Abstract: Sex steroid hormones regulate developmental programming in many tissues, including programming gene expression during prenatal development. While estradiol is known to regulate placentation, little is known about the role of testosterone and androgen signaling in placental development despite the fact that testosterone rises in maternal circulation during pregnancy and in placenta-induced pregnancy disorders. We investigated the role of testosterone in placental gene expression, and focused on androgen recepto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
36
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 66 publications
(93 reference statements)
0
36
0
Order By: Relevance
“…Functionally, PADs antagonize histone arginine methylation by coactivator associated arginine methyltransferase (CARM1) and protein arginine methyltransferase (PRMT1) (Wang et al 2004). In addition to PADs, multiple isoforms of histone lysine demethylase are expressed in caruncle tissue from gestation day 90 ewes (Cleys et al 2015). Interestingly, both epigenetic enzymes function as demethylases, which may be an important mechanism to regulate gene programs during pregnancy in ewe caruncle tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Functionally, PADs antagonize histone arginine methylation by coactivator associated arginine methyltransferase (CARM1) and protein arginine methyltransferase (PRMT1) (Wang et al 2004). In addition to PADs, multiple isoforms of histone lysine demethylase are expressed in caruncle tissue from gestation day 90 ewes (Cleys et al 2015). Interestingly, both epigenetic enzymes function as demethylases, which may be an important mechanism to regulate gene programs during pregnancy in ewe caruncle tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Contrary to mice, human trophoblast cells primarily express LIN28B (Canfield et al, 2018;West et al, 2018), and in this study we explored the possibility that androgen receptor (AR) is a potential target for LIN28B. AR localizes to villous stromal cells, cytotrophoblast, and syncytiotrophoblast in term placenta (Iwamura, Abrahamsson, Benning, Cockett, & di Sant'Agnese, 1994;Horie, Takakura, Imai, Liao, & Mori, 1992), and previous work in our lab suggests AR is involved in regulating placental angiogenesis through its interaction with VEGFA during pregnancy (Cleys et al, 2014). Considering AR is a known regulator of cell proliferation and migration in cancer cells, we recently postulated this also may be true in trophoblast cells during early placental development (McWhorter, Russ, Winger, & Bouma, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…One study demonstrated that both Prevotella intermedia and P. gingivalis are able to reduce testosterone to 5-alpha dihydrotestosterone (DHT) and induce DHT synthesis by fibroblasts [22]. More recently, a study investigating the role of androgen regulation during placentation showed that the placenta uses both androgen receptors and histone lysine demethylases to mediate androgen signaling and epigenetic regulation of gene expression during placental development [23]. These authors suggested that abnormal androgen signaling might alter placental development.…”
Section: Introductionmentioning
confidence: 99%